Perbandingan hidrograf banjir menggunakan beberapa metode perhitungan curah hujan efektif (studi kasus: Das Cisadane Hulu) - Orita Mega Delani; Bambang Dwi Dasanto (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2016)
Calculation of effective rainfall is an important step in hydrologic modelling. The used methods to calculate effective rainfall rarely observe watershed conditions on site. The objectives of the study is to determine the optimum method in calculating effective rainfall based on infiltration approach in Upper Cisadane Watershed and to analysis dominant characteristic of watershed on selected method. SCS-CN, Initial and Constant Rate Loss Method, and Green and Ampt Loss Method were the methods that used to estimate run off value in Upper Cisadane Watershed. The simulation was performed using HEC-HMS and tested using EF and RMSE on peak discharge and volume of hydrograph. The three events of peak discharge was chosen. Based on EF and RMSE test, Green and Ampt Loss Method model showed that simulated hydrograph was similar to measured hydrograph in Upper Cisadane Watershed with EF was 0.764 and RMSE was 5.93 m3/s. Based on the analysis, green and Ampt method is recommended to use on watershed with mountainous topographic and simillar on shape with Upper Cisadane Watershed.